A Complete 1H and 13C NMR Data Assignment for Three 3-[Substituted methylidene]-1H,3H-naphtho-[1,8-cd]-pyran-1-ones - Dimitar Stoitsov; Marin Marinov; Plamen Penchev; Maria Frenkeva; Neyko Stoyanov (Crystals, 2024)
A combination of 1D and 2D NMR techniques, including HMQC, HSQC, 1H-1H COSY and HMBC, was used to provide completely assigned 1H and 13C NMR data for the structures of three 3-[substituted methylidene]-1H,3H-naphtho[1,8-cd]-pyran-1-ones—3-[(4-methoxyphenyl)methylidene]-1H,3H-naphtho[1,8-cd]-pyran-1-one, 3-[(4-fluorophenyl)methylidene]-1H,3H-naphtho-[1,8-cd]-pyran-1-one and 3-[(thiophen-3-yl)methylidene]-1H,3H-naphtho[1,8-cd]-pyran-1-one. The heteronuclear coupling constants 1–4JCF and 3–4JHF were correspondingly determined. Additionally, IR and Raman spectral data were provided in support of the assigned structures.